Crise ambiental e Habermas : um enfoque sistêmico - Santos Filho, Agripino Alexandre dos (2011)
The aim of the research is to analyze the contributions of critical theory of society of Habermas, especially the habermasian concept of systemic crisis, for understanding the dynamics of contemporary environmental crisis. It is intended to investigate the contemporary environmental crisis, from the reconstruction of concepts of crisis and the nature and understanding the formation and characteristics of tardocapitalistas societies through the habermasian concept of systemic crisis. This research is fundamental or theoretical nature and uses the historical-critical method. It begins with a historical reconstruction of the concept of environmental crisis, from the ideas of crisis and nature, to analyze the current state of debate on the environmental crisis, by submitting the approaches of the scientific literature on the subject. Following is presented the concept of a systemic crisis of Habermas, built as part of its analysis of tardocapitalistas societies, in order to test the hypothesis that this concept contributes to the advancement of epistemological treatment on the environmental crisis. The relevance of this research urges the need to improve the debate on finding solutions to environmental problems that affect the welfare of human beings. The intended result is to an understanding of the environmental crisis, able to contribute to their proper treatment.